Digital Literation as A Teacher Solution in Learning The Digital Era and Pandemic Covid-19 - Jaenudin, Ahmad (Universitas Negeri Semarang, 2021)
This study aims to determine teachers’ problems in managing learning and to provide efforts to increase teacher competence in managing learning in the era of digital technology and the COVID-19 pandemic. The method used in this research is descriptive quantitative describing, explaining a phenomenon in various conditions or various research variables. This research was conducted in 5 public high schools in Pemalang Regency for the 2019-2020 school year. With a sample of 24 teachers who were randomly selected. Collecting data in this study were observation, interviews and documentation which were then analyzed by calculating the percentage of sample answers and tested using various theories. The results of this study indicate that the teacher actually already has the ability to plan the lesson as stated in the lesson plan (RPP), but in its implementation the teacher has difficulty managing learning. Other findings show that teachers’ mastery of digital technology in managing knowledge during the COVID-19 pandemic is not optimal. Based on the research results, learning in the digital and pandemic era requires the digital literacy of teachers in managing effective learning by providing training to teachers in the field of digital technology.